Fiscal difficulties of cities, the labor market, and health care. (19th December 2018) - Hsu, John; Newhouse, Joseph; Overhage, Lindsay Nicole; Zuvekas, Samuel
Abstract: We investigated labor force and health outcomes in cities experiencing fiscal difficulties to assess how those difficulties might impact their employees. We matched 23 cities with bond downgrades and 31 cities with stable bond ratings to sampling units in the Medical Expenditure Panel Survey. Starting the year before the downgrade and for the four subsequent years, the rate of separation from local public employment fell in the cities with downgrades relative to the comparison group. Self-reported health may have worsened, but there were no statistically significant effects on health care use or spending.